2009
DOI: 10.1371/journal.pone.0007850
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Dysregulation of MiRNAs by MYCN Amplification and Chromosomal Imbalances in Neuroblastoma: Association of miRNA Expression with Survival

Abstract: MiRNAs regulate gene expression at a post-transcriptional level and their dysregulation can play major roles in the pathogenesis of many different forms of cancer, including neuroblastoma, an often fatal paediatric cancer originating from precursor cells of the sympathetic nervous system. We have analyzed a set of neuroblastoma (n = 145) that is broadly representative of the genetic subtypes of this disease for miRNA expression (430 loci by stem-loop RT qPCR) and for DNA copy number alterations (array CGH) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(139 citation statements)
references
References 24 publications
4
131
1
3
Order By: Relevance
“…Other studies have confirmed direct binding of N-myc to the mir-17-92 promoter (50, 55), as well as a positive correlation between expression of MYCN and members of the mir-17-92 cluster in primary tumors and/or neuroblastoma cell lines (49,51,(55)(56)(57)(58)(59)(60)(61). As miRNAs simultaneously target a variety of different mRNAs, it became clear that activation of the mir-17-92 cluster enables N-myc to turn multiple cellular processes toward malignant transformation.…”
Section: N-myc Induces Mirna Expressionmentioning
confidence: 68%
See 2 more Smart Citations
“…Other studies have confirmed direct binding of N-myc to the mir-17-92 promoter (50, 55), as well as a positive correlation between expression of MYCN and members of the mir-17-92 cluster in primary tumors and/or neuroblastoma cell lines (49,51,(55)(56)(57)(58)(59)(60)(61). As miRNAs simultaneously target a variety of different mRNAs, it became clear that activation of the mir-17-92 cluster enables N-myc to turn multiple cellular processes toward malignant transformation.…”
Section: N-myc Induces Mirna Expressionmentioning
confidence: 68%
“…In one of the largest miRNA profiling studies in neuroblastoma so far, Bray and colleagues (49) profiled 430 miRNAs in a total of 145 primary neuroblastoma tumors, including 36 with MYCN amplification. They found both up-and downregulated miRNAs (14 and 23, respectively) when MYCN-amplified tumors were compared with nonamplified tumors.…”
Section: Tumor Sample Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Results show that the widespread deregulation of miRNAs expression in NB tumours is due to the chromosomal imbalances and overexpression of the MYCN (Bray et al 2009). MYCN might regulate C S Verissimo et al: Novel neuroblastoma targets www.endocrinology-journals.org the expression of miRNAs that play a role in NB proliferation (Chen & Stallings 2007).…”
Section: S Verissimo Et Al: Novel Neuroblastoma Targetsmentioning
confidence: 98%
“…There are indications that miRNA expression levels are predictive of clinical outcome. This suggests that miRNAs might be used as diagnostic markers and targets for NB therapy (Bray et al 2009). An overview of differently expressed miRNAs that have been proposed as NB therapeutic targets is provided in Table 3 and their expression in other tumours is given in Supplementary Table 2, see section on supplementary data given at the end of this article.…”
Section: S Verissimo Et Al: Novel Neuroblastoma Targetsmentioning
confidence: 99%